The Stumbling of Fatwa and Its Impact On Islamic Societies - Bensala, Youcef (Al-Basirah Journal, 2023)
The divergence in fatwas is a common matter; the Companions of the Prophet (pbuh) had different views on diverse issues; so had jurists to the extent that the volume of divergence in jurisprudence supersedes that of consensus. This is Allah’s fashion in his creature; He endowed humans with disparate abilities and intellects. However, what we witness today in light of the changing events and current manifestations is a discord, never sensed by Muslims before. As a consequence, the expert as well as the common man at large has started to question some fatwas on contemporary matters, as being driven by a political agenda rather than a legal Sharia-compliant principle. Is this type of fatwa of a contradictory nature or within the scope of conventional divergence? The importance of this research lies in exposing the real causes of stumbling in fatwas contemporarily fatwas, as well as the contributing factors of meticulosity it, in addition, Additionally, it aims to identify the concept of stumbling and reveal the fatwa parameters beside of fatwas, as well as the assistive instruments of regulation. The research comprises four chapters and a conclusion.